The choice of possible entrainers for the extractive distillation of binary mixture benzene – cyclohexane - V. M. Raeva; A. Y. Sebyakin; A. Y. Sazonova; A. K. Frolkova (Тонкие химические технологии)
The approaches to the formation of a set of possible entrainers for extractive distillation of the binary mixture benzene - cyclohexane are considered. The approaches are based on the analyses of concentration dependence of different excess thermodynamic functions.